Analisis Hukum Terhadap Putusan Pengadilan Negeri Jakarta Pusat Nomor 476/PID.SUS/2023 Tentang Tindak Pidana Pencucian Uang - Henry Afrillo; Hudi Yusuf (CV. ITTC INDONESIA, 2025)
Law enforcement against money laundering (ML) has an essential function in preserving the stability of the economy and financial systems of a country. The case involving the defendant Indah Harini, charged under Article 3 in conjunction with Article 2 section (1) point q of Law Number 8 of 2010, becomes the primary focus of this study. The crime committed by the defendant involved the diversion of funds that should have been returned to Bank BRI following a system error in crediting, as well as the use of those funds for personal purposes, leading to an eleven-year prison sentence along with a penalty of one billion rupiahs. The aim of this research is to investigate. whether the elements of illicit financial activities have been met, how the court's The panel of judges evaluated the. matter in question, and assess the conformity of the decision with the principles of justice and legal certainty. Furthermore, the research explores the function of banking institutions in the monitoring and reporting of suspicious transactions. The method employed in this research is document analysis and a case study utilizing a normative qualitative approach. The data includes court decisions, relevant regulations, and literature related to illegal financial crimes. According to the research findings, the defendant's actions fulfill the elements of money laundering, including the diversion of assets obtained through illegal activities, knowledge of the unlawful source of funds, and efforts to conceal the origin of the funds the court determined that the defendant was guilty and imposed a heavy prison sentence and fine. The ruling is considered consistent with the principle of legal assurance, but social justice aspects should also be taken into account. In this regard, the role of banking institutions is critical in detecting suspicious transactions and improving internal supervision through more advanced Anti Money Laundering (AML) systems, as well as enhancing cooperation with relevant authorities. It is expected that this research will contribute to the progress of criminal law, particularly in handling money laundering crimes, and provide recommendations for improvements in financial institution oversight and control systems to prevent similar cases in the future.